Whole genome sequencing reveals widespread distribution of typhoidal toxin genes and VirB/D4 plasmids in bovine-associated nontyphoidal Salmonella - Delgado Suárez, Enrique Jesús; Selem Mojica, Nelly; Ortiz López, Rocío; Gebreyes, Wondwossen A.; Allard, Marc W.; Barona Gómez, Francisco; Rubio Lozano, María Salud (2018)
Aedes aegypti is the primary urban mosquito vector of viruses causing dengue, Zika and chikungunya fevers –for which vaccines and efective pharmaceuticals are still lacking. Current strategies to suppress arbovirus outbreaks include removal of larval-breeding sites and insecticide treatment of larval and adult populations. Insecticidal control of Ae. aegypti is challenging, due to a recent rapid global increase in knockdown-resistance (kdr) to pyrethroid insecticides. Widespread, heavy use of pyrethroid spacesprays has created an immense selection pressure for kdr, which is primarily under the control of the voltage-gated sodium channel gene (vgsc). To date, eleven replacements in vgsc have been discovered, published and shown to be associated with pyrethroid resistance to varying degrees. In Mexico, F1,534C and V1,016I have co-evolved in the last 16 years across Ae. aegypti populations. Recently, a novel replacement V410L was identifed in Brazil and its efect on vgsc was confrmed by electrophysiology. Herein, we screened V410L in 25 Ae. aegypti historical collections from Mexico, the frst heterozygote appeared in 2002 and frequencies have increased in the last 16 years alongside V1,016I and F1,534C. Knowledge of the specifc vgsc replacements and their interaction to confer resistance is essential to predict and to develop strategies for resistance management.